Strategies for enhanced CWPO of phenol solutions - Inchaurrondo, Natalia Soledad (2012)
The performance of a commercial CuO/alumina catalyst used in the catalytic wet peroxide oxidation (CWPO) of 1. g/l phenol solutions is investigated in a batch reactor. The effect of temperature, catalyst load, hydrogen peroxide concentration and dosage strategies on phenol mineralization, hydrogen peroxide consumption efficiencies and catalyst stability was studied. Experiments were performed at 298, 323 and 343. K, using catalyst loads of 1. g/l or 25. g/l and concentrations of hydrogen peroxide 1.3, 2.6 and 3.9 times the stoichiometric requirement added at once or in distributed doses. The critical goal of the CWPO in terms of Process Intensification is to achieve total phenol mineralization working at optimal hydrogen peroxide consumption efficiencies while retaining catalyst stability. The present work highlights the complexity of this objective and shows viable working alternatives.Results indicate that high temperatures and concentrations of catalyst and hydrogen peroxide (added at once) can be employed when fast mineralization and high pH values are required in order to prevent catalyst leaching, although oxidant consumption efficiencies are then low. However, simultaneous high mineralization and hydrogen peroxide consumption efficiencies are obtained with a proper oxidant dosage strategy at high temperature, using high catalyst load. Then, hydrogen peroxide degradation into non-oxidising (parasitic) species is minimized with final TOC conversions close to 90%. The drawback of this strategy is that the rate of reaction is lower because of the limited amount of oxidant available.